2019
DOI: 10.1016/j.shaw.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Safety and Health Among Young Workers in the Nordic Countries: A Systematic Literature Review

Abstract: This review aimed to identify risk factors for occupational accidents and illnesses among young workers in the Nordic countries and to attain knowledge on specific vulnerable groups within the young working force that may need special attention. We conducted a systematic review from 1994 to 2014 using five online databases. Of the 12,528 retrieved articles, 54 met the review criteria and were quality assessed, in which data were extracted focusing on identifying occupational safety, health risk factors, and vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 80 publications
(138 reference statements)
1
60
1
5
Order By: Relevance
“…The disparity in the number of injuries among young workers has been reported in other countries (6,7). Evidence suggests that contributors to increased injury risk among younger workers include the following: workplace hazards associated with young worker jobs; violations of child labor laws; fast pace of work; minority status; and lack of skills, experience, supervision, and high-quality safety training.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The disparity in the number of injuries among young workers has been reported in other countries (6,7). Evidence suggests that contributors to increased injury risk among younger workers include the following: workplace hazards associated with young worker jobs; violations of child labor laws; fast pace of work; minority status; and lack of skills, experience, supervision, and high-quality safety training.…”
Section: Discussionmentioning
confidence: 98%
“…Evidence suggests that contributors to increased injury risk among younger workers include the following: workplace hazards associated with young worker jobs; violations of child labor laws; fast pace of work; minority status; and lack of skills, experience, supervision, and high-quality safety training. Young workers might be less likely to recognize workplace hazards, voice safety concerns, and be aware of their legal protections (3,(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…For a large number of young people who do not follow higher education after graduating from school, vocational education and training mark the first step into working life. Despite their recent entry into the labor market, young workers are already exposed to increased health risks and vulnerable to work-related diseases [3]. Studies have shown that the health burdens of apprentices are particularly high in occupations with high physical demands, such as the automotive industry and nursing care.…”
Section: Introductionmentioning
confidence: 99%
“…The musculoskeletal problems are signifi cant problem within the European Union with respect to ill health, productivity [18]. The reviews show that mechanical factors such as heavy lifting, psychosocial factors such as low control over work pace, and organizational factors such as safety climate are all associated with increased injury risk for young Nordic workers, this leads to the decrease in productivity due to absence from work, chronic diseases and health expenditures lead to estimated annual spending of 2.1 billion Euros in the Netherlands and about 45 to 54 million Dollars in the United States [19,20].…”
Section: Discussionmentioning
confidence: 99%